Factors influencing employee’s cyberloafing in an organization - Bello, Muhammed Adeyinka (2017)
Purpose – The purpose of the present study is to investigate antecedent factors that influences cyberloafing at the workplace so as to aid management of organizations in developing policies and measures that will help reduce the rate cyberloafing in the organization. Methodology – Data were collected from 175 employees who have an official appointment and internet access in an organization via convenience and snowball sampling. SPSS statistics 22 was utilised to analyse the collect data. Findings – The results show that cyberloafing was related to the four proposed factors namely social norms, job characteristics, job satisfaction, and job commitment. Though only social norms and job characteristics significantly influence employees’ cyberloafing at the workplace with the the other two factors not influencing it. Practical implications – In general the discussion in this study addresses practical implications of the research work.